Economics, economists, and expectations : microfoundations to macroapplications - Young, Warren, 1949-; Leeson, Robert; Darity, William A., 1953- (London ; New York : Routledge, 2004)
This book makes use of primary sources and previously unpublished material from such figures as Hicks, Hawtrey, and Hart. The accounts of the "founding fathers" of the models themselves are also presented here for the first time. The authors trace the development of different approaches to expectations from the likes of Hayek, Morgenstern, and Coase right up to more modern theorists such as Friedman, Patinkin, Phelps and Lucas. A necessity for economists across the world, this book will deserve its place upon many an academic bookshelf.
Includes bibliographical references (p. [140]-155) and index.
rpm 31/10/13
Loans
Keywords: Rational expectations (Economic theory)